Profil Kemampuan Dasar Resolusi Konflik Siswa Sekolah Menengah Atas di Kota Ambon - Huliselan, Neleke (Jurnal Bimbingan dan Konseling Terapan, 2017)
This study aims to determine the basic ability profile of conflict resolution in high school students in Ambon City. The study used quantitative descriptive. The population of the study were the students of class X at SMA Negeri 12 and SMA Negeri 7 Ambon, amounting to 312 people. Data collection tools are basic conflict resolution skills that have been tested for validity and reliability. Data analysis techniques use percentage test, and data are categorized using categorization level. The results showed: (1) the basic ability of conflict resolution of students mostly in the medium category that is as much as 211 people or 67.7%, which means that students have enough ability in conflict resolution. (2) Aspects The basic ability of conflict resolution of students who occupy the highest percentage is on aspects of perception ability (77%) and the lowest on aspects of emotional ability (67%).